Novel insights into mitochondrial gene rearrangement in thrips (Insecta: Thysanoptera) from the grass thrips, Anaphothrips obscurus - Hangrui Liu (Nature Portfolio, 2017)
Abstract We sequenced the mitochondrial (mt) genome of the grass thrips, Anaphothrips obscurus, which is highly rearranged and differs from the four thrips species reported previously in the arrangement of both tRNA genes and a protein-coding gene, nad3, and in the copy number of the control region (CR). We reconstructed the phylogeny of the thrips with mt genome sequences, and used it as a framework to gain insights into mt genome evolution in thrips. It is evident that A. obscurus is less rearranged in mt genome organization than the other four known thrips. nad3 is in its ancestral location in A. obscurus but was translocated in other four thrips. Also, A. obscurus has one CR, which is ancestral to hexapods whereas other thrips have two or three CRs. All of the five thrips whose mt genomes have been sequenced to date are from the subfamily Thripinae, which represents about a quarter of the species richness in the order Thysanoptera. The high variation in mt genome organization observed in a subfamily challenges our knowledge about animal mt genomes. It remains to be investigated why mt genomes evolved so fast in the subfamily Thripinae and how mt genomes evolved in other lineages of thrips.